The Portable MBA in finance and accounting - Livingstone, John Leslie; Grossman, Theodore (Hoboken, NJ : Wiley and Sons, 2009)
The Portable MBA in Fainance and Accounting, Fourth Edition has been entirely revised and updated. This bestselling reference is packed with in-depth, authoritative coverage of crucial topics in finance and accounting. Professors Grossman and Livingston have assembled the best contributors on the subject, with chapters from top professors and practitioners in finance, accounting, and law. These expert contributors provide clear, jargon-free explanations of key finance and accounting topics to help business professionals demystify even the most complex subjects.
Understanding financial statements / Les Livingstone -- Analyzing financial statements / Les Livingstone -- Analyzing business earnings / Virginia Earll Soybel -- Discounted cash flow / James A. Elfter -- Capital structure / Craig A. Stephenson -- Planning capital expenditure / Steven P. Feinstein -- Global finance / Michael J. Riley -- Choosing a business form / Richard P. Mandel -- Taxes and business decisions / Richard P. Mandel -- The integrity of financial reporting / Les Livingstone -- Forecasts and budgeting / Robert F. Halsey -- Cost structure analysis, profit planning, and value creation / William C. Lawler -- Activity-based costing / William C. Lawler -- Business planning / Andrew Zacharakis -- Financial management of risks / Steven P. Feinstein -- Business valuation / Michael A. Crain -- Profitable growth by acquisition / Richard T. Bliss -- Outsourcing / Theodore Grossman -- Information technology and you / Dawna Travis Dewire -- Information technology and the firm / Dawna Travis Dewire -- Careers in finance / Tracee Petrillo and Ralph J. Constantino.
Includes bibliographical references and index.
Print version record.
English.
John Wiley and Sons
Keywords: Business enterprises -- Finance; Accounting; BUSINESS & ECONOMICS -- Corporate Finance; BUSINESS & ECONOMICS -- Finance; Accounting; Business enterprises -- Finance